Panic Disorder Neurobiological and Treatment Aspects - Nardi, Antonio Egidio; Freire, Rafael Christophe R. (Springer International Publishing : Imprint: Springer, 2016)
The book focuses on the neurobiological and treatment aspects of panic disorder. It describes the most recent research data and pharmacological therapeutic aspects of panic disorder. The biochemical, respiratory, imaging, and translational aspects will be together with diagnostic and pharmacological discussion. We have the collaboration of important and recognized researchers from various countries - Brazil, USA, Italy, Spain, United Kingdom, and Switzerland - all of them with a continuous and relevant work on anxiety disorders. "Panic Disorder: Neurobiological and Treatment Aspects" is intended to be a reference book for those who research or treat panic disorder and anxiety disorder patients.